SINERGITAS PEMERINTAHAN DESA DALAM PEMBENTUKAN PERATURAN DESA - Anggalana (Law Faculty of Universitas Bandar Lampung, 2020)
The synergy between the Village Head and the Village Consultative Body (BPD) in the Process of Forming Village Regulations, is manifested in the form of partnership, where the position between the Village Consultative Body (BPD) and the Village Government is in line with the authority possessed in different formations, starting from the stages of planning, drafting, discussing, determining and determining enactment and dissemination of Village Regulations. In addition, the Village Consultative Body (BPD) has the authority to also have the oversight function of the implementation of the Village Regulation by the Village Head. Meanwhile, if the Village Regulation cannot be carried out properly and is unable to bring justice to the community, the Village Consultative Body (BPD) has the authority to cancel the Village Regulation that has been jointly determined, with the Village Head or that has been implemented by the Village Head where the Village Consultative Body (BPD) can submit cancellation. The Village Regulation is sent to the District Government through the District Head to conduct an evaluation of the Village Regulation